(3QSGdI aj GdCLhHI Ydi HYV eG aj GdeWhds - (3eLghds
(3ChdgG (B:s
(3fMeOc jG ef aJM CHhGH GdeYGfj hNRGFf GdHjGfhHYO adeG CQGO CYde GdYdeGA TjN GdESdGeOQj RGOg GdSjO YHO GddgCf jYbO eLdSG dGeJMGf WdHI GdYdhe ef WdGH GdQhS Yjf ehVY GdGeJMGf ef GdeWhd ef bhdg hCUd GdNWGH Cf jchf deYjfaGfJNHfG ef CSFdI ObjbI eY CLhHI GdMbjbI YQVfG Ydjges
(3BNQgG (B:s
(3GdLhGH GdGeJfGY HGYJHGQ GdESfGO GdeNGWH hGdJMbjb dCUd GdaYd aPcQ dh jOd Ydi Cf GdQDjI HeKGHI ef GdaVGYI JeJfY eYgeG QDjI GdeNGWHs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdHdGZIs